2014
DOI: 10.1038/sc.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

Long-term urological management in spinal injury units in the UK and Eire: a follow-up study

Abstract: Aims: The majority of patients with spinal cord injury (SCI) will develop neurogenic lower urinary tract dysfunction (NLUTD). These patients require a long-term urological follow-up. The follow-up protocol has varied across SCI units in the United Kingdom and Eire. We reviewed the long-term management in the SCI units to identify changes in practice over a decade and compared them to current guidelines. Methods: We present results of a review of all SCI centres in the United Kingdom and Eire on their long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…After duplicates removal (n = 100), 147 of 180 screened articles were excluded because they were not related to the neuro-urological follow-up. In all, 23 of 33 full-text articles were included in the quantitative synthesis [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Thus, 10 articles were excluded because they did not bring additional information on the neuro-urological follow-up (six review articles, two case-reports, one animal model, one cross-sectional study) [25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicates removal (n = 100), 147 of 180 screened articles were excluded because they were not related to the neuro-urological follow-up. In all, 23 of 33 full-text articles were included in the quantitative synthesis [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Thus, 10 articles were excluded because they did not bring additional information on the neuro-urological follow-up (six review articles, two case-reports, one animal model, one cross-sectional study) [25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Burki et al [23] addressed the effects of the European Association of Urology (EAU) Guidelines on Neuro-Urology and the proposed British Guidelines for the Urological Management of Patients with SCI in the UK. These authors concluded that there was a continued lack of high-quality evidence to support an optimal long-term follow-up protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the UK showed an increase in adherence to the guidelines in recent years. A French survey observed that routine follow-ups including UDS were performed by 56% of urologists and 83% of physiatrists, most often annually [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Studies from UK showed improving compliance with guidelines in recent years, but most institutions were still not performing regular follow-up urodynamics. [ 21 22 ] A survey from France showed that routine follow-up urodynamics was performed by 56% of urologists and 83% of physiatrists, most often on an annual basis. [ 23 ] However, only 12% urologists in the Netherlands performed routine follow-up urodynamics despite European Association of Urology (EAU) guidelines recommendations.…”
Section: Adherence To Clinical Guidelinesmentioning
confidence: 99%